Study on crop residue coverage in the state of Iowa and its importance in regional water supply - Mohammad Rafayet Hossain (The Egyptian Journal of Remote Sensing and Space Science, 2020)
Transfer of nutrients and other toxic chemicals from agricultural fields to ground and surface water sources have become a major concern for regional planners in the State of Iowa. It depends on the strength of soil, residue coverage, terrain condition, and annual rainfall. South Fork portion of the Iowa River is fed by Tipton Creek, Honey Creek, Beaver Creek etc. watersheds and this area are located close to cities like Iowa Falls, Marshalltown, and Eldora. Land cover in this area is dominated by corn and soybean production. Presence of higher residue coverage means no-tillage farming practice in agricultural fields and it reduces the force with which raindrops fall on the soil. Correlation between residue coverage and Normalized Difference Tillage Index (NDTI) has been used as the method to identify the presence of tillage practice in agricultural fields. Residue coverage was less than 30% in 352 agricultural fields located adjacent to the South Fork portion of the Iowa River and the positive correlation between NDTI and residue coverage represents the effectiveness of data calculation procedure. A solution of these problems will require both policy and design based initiatives over a long period of time and implementation of existing natural resource management laws.